Study of Microstructure and Optical Properties of Fe2O3/TiO2 Composites as Functional Materials - Rendy Muhamad Iqbal; Erwin Prasetya Toepak; Dyah Ayu Pramoda Wardani; Elda Alyatikah; Stevin Carolius Angga; Luqman Hakim (Jurnal Sains dan Terapan Kimia, 2022)
Semiconductors have conductivity levels between insulators and conductors which can be applied in various fields such as photocatalytic, adsorption, and Dye Sensitizer Solar Cell (DSSC). However, some semiconductors are only active under ultraviolet light, therefore to improve their utilization, modifications are made by producing a hybrid combination of two or more materials or dopping materials. This study aims to obtain a semiconductor material with a low band gap energy from the Fe2O3/TiO2 composite material. Fe2O3/TiO2 composites were synthesized by the solid-state method and characterized by XRD, SEM-EDX, and UV-Vis. The characterization using XRD showed the peak intensity of TiO2 and Fe2O3. The morphology of the material obtained using SEM-EDX showed an even distribution of particle size, as well as the distribution of Ti, Fe, and O elements. The optical properties of the composite showed strong absorbance in the UV region for higher TiO2 compositions. On the other hand, composite materials with a higher Fe2O3 composition showed stronger absorbance in the visible light region.